Development of Cream Soup Made From Combination of Black Soybean (Glycine soja L. merrit) and Red Rice (Oryza nivara) as an Alternative Functional Food for Menopausal Women - Estuti, Wiwit; Marliyati, Sri Anna; Damanik, Muhammad Rizal Martua; Setiawan, Budi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
This study aimed to develop an organoleptic acceptable cream soup formula made from combination of black soybean (Glycine soja L. merrit) and red rice (Oryza nivara) which met the nutritional requirements and contained antioxidants in the form of snack as a functional food for menopausal women. This study used a completely randomized design (CRD) with three treatment levels combination of black soybeans and red rice, namely F1 (80:20), F2 (70:30), and F3 (60:40). The results of the hedonic organoleptic test showed that the selected formula was F1 functional cream soup product. The nutrient content analysis showed that the product contained 1.98% water, 1.88% ash, 4.00% fat, 13.36% protein, 78.76% carbohydrates, 17.87% total dietary fiber, 10.71% soluble dietary fiber, 162.59 μg/g total isoflavones, and 254.58 μg/g total anthocyanins. Each portion of the F1 product could contribute 10.66% and 11.73% of the recommended dietary allowances (RDA) for energy and protein for women of menopausal age, respectively. Each portion also had an antioxidant activity of 723.73 mg/100 g (AEAC). The product is safe to consume because its total microbial content was 3.4 x 102 colonies/g. The resulting product has the potential to be a functional food due to its fiber, total isoflavones, and total anthocyanins contents, as well as its antioxidant activity.